Peran Andragogi dalam Mempersiapkan Orang Tua sebagai Pendidik Anak Usia Dini - Jefrianus Da Silva; Ruth Judika Siahaan (Institut Nalanda, 2024)
Many parents still lack the necessary knowledge and skills to support optimal child development. The purpose of this study is to describe the role of Andragogy, as an adult education approach, offering a solution by customizing learning based on parents' needs and motivations. This approach can overcome three main challenges faced by parents: lack of knowledge about ECD, limited time for training, and low motivation and support in the process of learning and shaping children's spirituality and character. The researcher uses a qualitative method or literature study where the researcher provides solutions to the problems raised by collecting various theories and information from literature materials such as books, dictionaries, journals, Bibles, and online media.